Bioinformatics tools @ NBBNet: online infrastructure for the management and analysis of biological data - Mohd Firdaus Raih; Mohd Yunus Sharum (Penerbit UKM, 2006)
The use of informatics tools for the management and analysis of sequences for nucleic acids and proteins has resulted better throughout capability of wet lab research work to infer biological data to functional biological information. The field of computational biological information management and analysis is generally known as bioinformatics. We discuss some tools and processes which have been developed or integrated into a data management and information presentation pipeline by the Malaysian National Biotechnology and Bioinformatics Network. Central to this is the Bioinformatics Tools @ NBBnet online infrastructure system. This infrastructure system utilizes grid computing technology. In addition, the deployment of niche databases and database shells for research applying specific datasets such as a particular protein function, protein family or genomes have been discussed.